THE EFFECT OF GOOD CORPORATE GOVERNANCE ELEMENTS, LEVERAGE, FIRM AGE, COMPANY SIZE AND PROFITABILITY ON EARNING MANAGEMENT (Empirical Study Of Manufacturing Companies in BEI 2014 – 2016) - Erik Indracahya; Dewi A. Faisol (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
The aim of this research to analyzed the impact of Good Corporate Governance, Leverage, Firm Age, Company Size and Profitability on Earning Management. The data used in this research was a secondary data in the form of financial statements from each company reported to BEI period 2014 – 2016 that resources from Indonesia Stock Exchange (BEI) website. The sample was used in this research as much 50 manufacturing companies from 144 companies that listed in Indonesia Stock Exchange (BEI) period 2014 – 2016. The sampling were used purposive sampling method. Analyzed of data that used in this research was multiple regression. This result indicated Good Corporate Governance has a negative and significant impact on Earning Management. Leverage has a positive and significant impact on Earning Management. Firm Age do not has a positive and not significant impact on Earning Management. Company Size do not has a positive and not significant impact on Earning Management and Profitability has a positive and significant impact on Earning Management. The regression model was obtained from this research indicated that independent variable can explain the dependent variable amounted 13.1% and the rest amounted 86.9% be affected from other variable were not examined in this research.